ANALISIS YURIDIS TERHADAP PUTUSAN HAKIM DALAM PERKARA ASUSILA YANG DILAKUKAN ANGGOTA MILITER (STUDI PUTUSAN 26-K/PM.I-05/AD/VII/2024): Legal Analysis Of Judges' Decisions In Cases Of Abusive Offences Committed By Military Members (Study Of Decision 26-K/Pm.I-05/Ad/Vii/2024) - Diah Ayu Putri Arini; Sutrisno (Faculty of Law, Universitas Trisakti, 2025)
This study aims to legally analyze the judge's decision in an immoral case committed by a military member, with a case study on Military Court Decision Number 26-K/PM.I-05/AD/VII/2024. Thus, the problem of this study is whether the perpetrator's actions meet the qualifications of a combined crime against morality and pornography so that Article 281 point 1 of the Criminal Code that was imposed can be juxtaposed with Article 4 paragraph (1) of Law Number 44 of 2008 concerning Pornography? This study uses a normative legal research method with a descriptive-analytical approach. The data used consists of primary and secondary legal materials collected through literature studies. The analysis is carried out qualitatively and conclusions are drawn deductively. The results and conclusion of the study show that the perpetrator's actions can be categorized as a combined criminal act, namely violating Article 281 point 1 of the Criminal Code, Article 285 of the Criminal Code, and Article 4 paragraph (1) in conjunction with Article 35 in conjunction with Article 9 of Law Number 44 of 2008 concerning Pornography, so that the perpetrator can be said to fulfill the qualifications for a combined criminal act.